Analysis of Social Change in Rural Communities Due to the Influence of Urbanization and Globalization in Indonesia - Junaedi Junaedi; Diki Dikrurohman; Abdullah Abdullah (PT Publikasiku Academic Solution, 2023)
Urbanization and globalization have had a major influence in accelerating social change in society, including rural communities. These changes can have an impact on the values, culture, and social structure of rural communities. Therefore, this study aims to analyze social changes in rural communities due to the influence of urbanization and globalization in Indonesia. This study aims to analyze social changes in rural communities due to the influence of urbanization and globalization in Indonesia. This study uses a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. Respondents taken in this study are from rural communities who have experienced the effects of urbanization and globalization in rural areas in Indonesia. The results of the study show that the influence of urbanization and globalization has accelerated social change in rural communities in Indonesia. Some of the social changes that have occurred include changes in values, culture, and patterns of behavior in rural communities. This can be seen from changes in lifestyle, consumption patterns, mindsets, and patterns of social interaction. This social change had an impact on a shift in the social structure of rural communities, where there was a shift from an agrarian society to an increasingly urbanized society.